Impacted Sharp Oesophageal Foreign Bodies—A Novel Technique of Removal with the Paediatric Bronchoscope - Mitra, Aparajita (J Trop Pediatr, 2016)
Sharp foreign bodies in the oesophagus may present as an entirely asymptomatic child with only radiological evidence but require emergent surgical management. Safety pins, razor blades and needles are a few of the commonly ingested sharp objects in developing countries. The open safety pin is a particularly interesting clinical problem, as the management depends on its location and orientation. Many methods and instruments have been used over the years to remove them from the upper digestive tract. We present a novel method using the rigid paediatric bronchoscope and alligator forceps for the extraction of this unusual foreign body from the oesophagus of a 6 year old girl.